Strategic alliances in container shipping: A review of the literature and future research agenda - Mohammad Ghorbani; Michele Acciaro; Sandra Transchel; Pierre Cariou (Maritime Economics & Logistics, 2022)
Strategic alliances are the most common type of collaboration agreement used by shipping lines to provide worldwide maritime container transport services. Since their first appearance just before the mid-1990s, they have progressed to account for 90% of global container shipping capacity with the top eight container operators organizing today their East/West route services through one of the main three strategic alliances. This paper reviews comprehensively and critically the literature on the subject, over 25~years of research on this topic. This includes 85 articles published in peer-reviewed journals between 1994 and 2019, and analyzed and grouped into three main research areas: formation, management, and optimization of strategic alliances. The output of the analysis is then used to provide a future research agenda .
Keywords: 380; Container shipping; Strategic alliances; Operational collaboration; Liner shipping; Vessel sharing